A CONSTRUÇÃO DA PERSONALIDADE DE MARIANO NO DISCURSO LITERÁRIO EM O GALO DE OURO, DE RAQUEL DE QUEIROZ - Silva, Francisco Geimes de Oliveira; Fernandes, Liduína Maria Vieira (Revista Literatura em Debate, 2013)
Este artigo objetiva analisar as construções discursivo-literárias de estética do discurso, do cotidiano e do caráter psicológico do personagem Mariano no romance urbano O Galo de Ouro (1986), de Raquel de Queiroz. Baseamo-nos em estudos de Amaral (2000); Barthes (1987); Bakhtin (1992; 1993; 1998); Cancho (2004); Lukács (2000); Marchese (1987) sobre a Teoria da Literatura, Análise do Discurso e Linguística.THE CONSTRUCTION OF THE PERSONALITY OF MARIANO IN LITERARY DISCOURSE IN THE O GALO DE OURO, OF RACHEL DE QUEIROZ This article aims to analyze the discursive constructions-literary aesthetics of speech, of the daily life and the character of psychological character Mariano urban romance the O Galo de Ouro (1986), Rachel de Queiroz. We base this on studies of Amaral (2000); Barthes (1987); Bakhtin (1992; 1993; 1998); Cancho (2004); Lukacs (2000); Marchese (1987) on the theory of Literature, Discourse Analysis and Linguistic.